2015
DOI: 10.1007/s11661-015-3061-7
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Dynamic Strain Aging in Ultrafine-Grained Titanium

Abstract: Dynamic strain aging (DSA) in coarse-grained (CG) titanium is usually observed at intermediate to high temperatures 473 K to 973 K (200°C to 700°C) and is characterized by serrations in the stress vs strain curves. In the present work, despite the absence of apparent serrations, ultrafine-grained titanium (UFG Ti) undergoes DSA at room temperature, exhibited through an abnormal increase in the elastic limit and negative strain rate sensitivity. This effect is observed at 293 K (20°C) in the strain rate interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…An average negative, value of the strain rate sensitivity in Figure 2(b) was found to be around m = -0.02, which is consistent with those reported in the literature 14,15,17 for stainless steels and ultrafine grained titanium in the DSA interval of temperatures. Another point worth noticing in Figure 2(b) is the clear existence of two well defined peaks in the ultimate stress around 300°C and 420°C for the 3.5 x 10 -4 s -1 strain rate curve.…”
Section: Resultssupporting
confidence: 90%
“…An average negative, value of the strain rate sensitivity in Figure 2(b) was found to be around m = -0.02, which is consistent with those reported in the literature 14,15,17 for stainless steels and ultrafine grained titanium in the DSA interval of temperatures. Another point worth noticing in Figure 2(b) is the clear existence of two well defined peaks in the ultimate stress around 300°C and 420°C for the 3.5 x 10 -4 s -1 strain rate curve.…”
Section: Resultssupporting
confidence: 90%
“…1 that the activation volume is inversely proportional to both the strain-rate sensitivity and yield stress.The yield stress of UFG titanium is approximately twicethat of coarse-grained CP titanium. The activation volume of UFG pure titanium is~40b 3 , where b=0.289 nm is the Burgers vector in hexagonal titanium.Thisrepresents a significant reductionintheactivation volume, compared with 80b 3 for coarse-grained CP titanium [10],suggesting a change in the rate controllingmechanism.…”
Section: Strain Hardening and Strain-rate Sensitivitymentioning
confidence: 83%
“…The average grain size of the as-received UFGtitanium was ~120nm.The microstructure of cross-section of as-received titanium rod was observed by Lopeset al [10] usingTEM as shown in Fig.1. Dynamic compression tests were performed using a split Hopkinson pressure bar (SHPB).…”
Section: Experimentalproceduresmentioning
confidence: 92%
See 2 more Smart Citations